A Study of Selected Epidemiological Poems about the Interactions of Human Nature in the New Normal World (Zien Journal of Social Sciences and Humanities, 2022)
Emerging patterns of behavior and relationships are now the norm in society due to the global spread of the Corona Virus sickness in the 21st century, which shocked people's sensitivities. The humannature relationship is one area where interactions have changed. There have been reams written about the environmental impact of human activities, with some researchers attributing environmental problems to patriarchal societal conditioning and calling for the end of all dualisms (but especially the dualism between humans and the rest of nature). However, few accurately portray how people feel about the natural world in the post-industrial era. This paper uses eco-critical theory to analyze a selection of pandemic poems in the context of new forms of ecological engagement. The research finds that the chosen poets have portrayed the new normal as a panacea to the enduring environmental difficulties that have eluded many solutions over the last decades. It suggests exploring environmentally friendly adaptation discourse in the new everyday world. It is crucial for spreading awareness about the need for environmental sustainability and encouraging research into the relationship between content and form in eco-critical discourse.